THE INFLUENCE OF TERMINAL VALUE, INSTRUMENTAL VALUE, AND GREEN BRAND POSITIONING ON GREEN PURCHASE INTENTION THROUGH GREEN ATTITUDE AS A MEDIATING VARIABLE (Study on Automotive Companies Implementing Green Company) - Arkan, Irsyad; Artanti, Yessy; Iriani, Sri Setyo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Thisi studyi aimsi toi examinei thei effecti ofi Terminali Value,i Instrumentali Value,i andi Greeni Brandi Positioningi oni Greeni Purchasei Intentioni withi Greeni Attitudei asi ai mediatingi variable.i Thei researchi methodi usedi isi descriptivei quantitativei withi Partiali Leasti Squarei (PLS)i analysisi toi testi thei causali relationshipi betweeni variables.i Thei researchi populationi isi prospectivei LCGCi cari consumersi ini Indonesiai withi characteristicsi agedi 25-35i years.i Thei resultsi showedi thati Terminali Valuei andi Greeni Brandi Positioningi havei ai positivei andi significanti influencei oni Greeni Attitude,i whilei Instrumentali Valuei hasi noi significanti effect.i Greeni Attitudei itselfi isi proveni toi playi ai mediatingi rolei thati strengthensi thei relationshipi betweeni thei independenti variablesi andi Greeni Purchasei Intention.i Thei implicationsi ofi thisi studyi providei insightsi toi marketersi andi automotivei companiesi toi furtheri emphasisei terminali valuei andi environmentallyi friendlyi positioningi strategiesi ini theiri marketingi campaignsi toi increasei thei purchasei intentioni ofi greeni productsi amongi consumers.